Generalized coordinated multipoint framework for 5G and beyond - Solaija, Muhammad Sohaib J.; Salman, Hanadi; Kihero, Abuu B.; Sağlam, Mehmet İzzet; Arslan, Hüseyin (Institute of Electrical and Electronics Engineers Inc., 2021)
The characteristic feature of 5G and beyond networks is the diversity of services, which is required to support different user needs. However, the requirements for these services are often competing in nature, which impresses the necessity of a coordinated and flexible network architecture. Although coordinated multipoint (CoMP) systems were primarily proposed to improve the cell edge performance in 4G, their collaborative nature can be leveraged to support the diverse requirements and enabling technologies of 5G and beyond networks. To this end, we propose the generalization of CoMP to a proactive and efficient resource management framework capable of supporting different user requirements such as reliability, latency, throughput, and security while considering network constraints. This article elaborates on the multiple aspects, inputs, and outputs of the generalized CoMP (GCoMP) framework. Apart from user requirements, the GCoMP decision mechanism also considers the CoMP scenario and network architecture to decide upon outputs such as CoMP scheme or appropriate coordinating clusters. To enable easier understanding of the concept, a case study illustrating the effect of different combinations of GCoMP framework's outputs on varying user requirements is presented.
Keywords: 5G Mobile Communication; Throughput; Resource Management; Wireless Communication; Reliability; Intercell İnterference; Dynamic Scheduling; 5G; 6G; Backhaul; Clustering; Coordinated Multipoint (CoMP); Energy Efficiency; Flexibility; Generalized CoMP (GCoMP); Multi-TRP MIMO; Quality of Service (QoS); Radio Resource Management (RRM)